Gain a baby lose a tooth: is there an association between periodontitis and preterm birth? - Bartha, Valentin; Steinmacher, Sahra; Wittlinger, Rebekka; Boutin, Sébastien; Pauluschke-Fröhlich, Jan; Ohle, Christiane von; Brucker, Sara; Bruckner, Thomas; Wolff, Diana (Journal of Clinical Medicine, 2022)
Preterm birth serves as one of the leading causes of neonatal mortality worldwide. The underlying mechanisms that contribute to preterm birth are not yet fully understood. However, an association between periodontitis and preterm birth has been proposed. The periodontal status and presence of periodontal pathogens in women with different birth outcomes have been previously examined. However, varying definitions of periodontitis and different microbiological methods make their interpretation challenging. The aim of this case-control study on women with and without preterm birth was to investigate their periodontal status using the current classification system for periodontal diseases. Moreover, differences in the periodontal microbiome of the study participants were investigated. Therefore, we collected data on oral and periodontal parameters in 77 puerperal women divided into two groups based on gestational age at delivery: 33 patients with preterm birth (PTB, <37 weeks) and 44 patients with term birth (TB, >37 weeks). These data included pocket probing depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), gingival-bleeding index, DMFT index, and gynecologic and dental history. In addition, their oral microbiome was explored. Median CAL and percentage PPD ≥ 4 mm were significantly higher in the PTB group than in the TB group (p = 0.0128 and p = 0.047, respectively). Birth weight was significantly higher in periodontally healthy women than in those with gingivitis (p = 0.0078) or periodontitis (p = 0.0127). The periodontal microbiome differed significantly between groups. Our results are underlining the possible association between periodontitis and preterm delivery. Women with periodontitis had babies with significantly lower birth weights. The microbiome varied between the groups.
Gesehen am 01.02.2023